Wealth Management, Asset Allocation and its relevance in the Singapore context - Ng, Kian Soon (2008)
This paper tackles the necessity of wealth management for individuals, looks at the current trends of wealth management in the country. It will discuss the details of the different investible asset classes in Singapore and provide recommendation on how an individual can structure his investments across different asset classes to achieve a sizeable portfolio by the time he retires with the objective to earn good returns over the long term.